(untitled) (Ozone Therapy Global Journal, 2013)
We read the letter entitled “Rectal insufflations are a valid way in ozonetherapy” by Martínez- Sánchez et al. (Revista Española de Ozonoterapia. 2012, Vol. 2, nº 1, pp. 233-235) as a feedback on our article “Oxygen-Ozone Therapy is at a Cross-Road” (Rev. Esp. Ozono. 2011, 1(1): 74-86). As we have been involved in this topic for longer than two decades, we felt the duty to express some reservation about the validity of the ozone administration via rectal route as well as the expanding use of infusing ozonated saline. It is obvious that the ozone administration via rectal route is the most simple and cheap way to administer ozone. However, while the physician intends to administer a total amount of 6 mg, he cannot be ever sure which is the effective ozone dose because: i) in the colorectal lumen there are feces, mucopolysaccharides that variably react and neutralize some of the administered ozone; ii) part of the gas may be involuntarily eliminated. Moreover, it must be clear that the remaining ozone is never absorbed by the rectal mucosa because it immediately reacts with the lining fluid. On the other hand, the generated H2O2 last only about 20 sec and only some peroxidation products can be absorbed and they have been measured in the portal and jugular veins. To the best of our knowledge, the experimental work conducted in rabbits in 2000 is the only one published clarifying this point.1 Therefore, the dose of ozone acting as a really effective prodrug remains uncertain and variable, and the procedure remains empirical. Moreover, in Europe at least 40% of patients refuses the rectal administration.